mbalance between the executive and legislative branches In the Constitution of the Republic of Iraq for 2005: A comparative study - حسن, حيدر محمد (Journal of Legal Sciences, 2018)
The most important right parliamentary system features it is based on three key elements must be met in order for this system is characterized by Balbrlmana, and these features lie in cooperation and balance between the executive and legislative branches also lies in the equality between the two branches, and this can not be achieved unless there is a mutual understanding between them, and this understanding can only be achieved if all possessed the power of the media and the influence of pressure is what makes other power stands at a certain pointTherefore constitutional rules came in this system to decide the legislative authority of certain rights exercised in the face of the executive branch and check use effective on its work and behavior control, and in an interview these rights the Constitution puts at the disposal of the executive power and the means that can by which affect not only the work of the legislature, but in the presence He also realized that the balance between the branchesNevertheless, some constitutions have embraced solutions bucked the implications part of these rules, while made it difficult for the ministry to resort to dissolve the council when his inability to discharge of the duties, because of the suspension of this solution on the approval of the Council itself, the time which makes it easier for the council that topples the ministry. Has been featured prominently in the approach taken by the Constitution of the Republic of Iraq for the year 2005, when it actually disrupted the ministry the authority to dissolve the House of Representatives in what was dubbed the hands of the Council to dismiss the ministry and this approach is contrary to sound legal assets also represents a breach Pena conditions of oversight and accountability, and a deviation from the fixed to the parliamentary system Qaeda.